An exploratory analysis on diastolic function in the intensive compared with less intensive blood pressure control to prevent adverse cardiac remodelling in children with chronic kidney disease (HOT-KID): a parallel-group, open-label, multicentre, randomised, controlled trialResearch in context - Haotian Gu; John M. Simpson; Janette Cansick; Eric Finlay; Rodney Gilbert; Andrew Lunn; Heather Maxwell; Henry Morgan; Mohan Shenoy; Rukshana Shroff; Pushpa Subramaniam; Jane Tizard; et al. (EBioMedicine)
Summary: Background: Relationship between blood pressure (BP) control and left ventricular (LV) diastolic function in children with chronic kidney disease (CKD) is uncertain. The aim of this study is to investigate whether achieving lower BP yields a favourable impact on diastolic function. Methods: We performed an exploratory analysis in the HOT-KID, a parallel group, open-label, multicentre, randomised, controlled trial (ISRCTN25006406). Children with CKD were randomised to standard (50th–75th percentile) or intensive (<40th percentile) standardised office systolic BP targets. Echocardiograms were performed at baseline and at follow-up visits. Diastolic function was assessed by early (E) and late mitral inflow (A) E/A ratio, mitral annular motion of myocardial relaxation (e’) and atrial contraction (a’) velocity, LV compliance of E/e’ and e’/a’ ratio, and left atrial volume index (LAVi) by a blinded observer. Findings: There was a difference in the average annual rate of change in E/A ratio (difference in means −0·07 per year, 95% CI: −0·14 to −0·01), septal e’ (difference in means −0·003 m/s per year, 95% CI: −0·005 to 0·001), and LAVi (difference in means 0·82 ml/m2 per year, 95% CI: 0·22–1·42) in the standard (n = 60) compared to the intensive treatment arm (n = 64). However, the average annual changes in all other diastolic function measures were similar between standard and intensive treatment groups. There was no difference for overall adverse events or serious adverse events between the two treatment groups. Interpretation: Our exploratory analysis in a small, open label RCT suggests that achieving lower blood pressure may favourably impact some measures of LV diastolic function in children with CKD. Funding: British Heart Foundation (PG/11/90/28,994); The authors MDS, PJC acknowledge financial support from the Department of Health via the National Institute for Health Research (NIHR) comprehensive Biomedical Research Centre and Clinical Research Facilities awards to Guy’s and St Thomas’ NHS Foundation Trust in partnership with King’s College London and King's College Hospital NHS Foundation Trust. There are no relationships with industry.